Revisitação do romance O Cortiço, de Aluísio Azevedo: da estética naturalista à estética tropicalista - Chapski, Rita (2014)
The current survey approaches a study of revisiting the romance O Cortiço, by Aluisio Azevedo, on the clef of Brazilian Realism. Its pragmatic center is on an enigmatic game of a literary meaning, which the narrator author solidaires himself, testing the Brazilian female world. From this complicity, we have decided on a methodology of aesthetic that transgress the gadgets used by its own positive methodology to the orthodoxism of the XIX century. The feminine erotism brings the action showed by the main characters: Bertoleza, Rita Baiana, Pombinha, Léonie and Estela, taking them to a resistant denounce action on a board of a double social representation, house slum tenement. Arises from this structural inversion our problem: the female characters are predictable on the subject of the romance or they transgress the patriarchalism under a trying stare of the Alusiana aesthetic? On the diagnostic of hypotheses launched on this essay, we look for answers to the result of this social contamination under the scientificism of the occidental reason, on the scope of the literary of the XIX century. Although, the rupture seen on the mobility of reports of the female characters actions we repeat on the browse of the main social homogeneity, modified through operative parody present on the performance of each fictional characters. On a continental scenery, the reality of the romance is highlighted trough the analogy with the reality The Country of America , interlacing the vectors white house x half breed slum tenement in the process of creolization. The resultant of this Revisitation is pointed to a poetic relation of the creole culture (Gissant, 2005), and the transgression of the interdict (Baitalle, 2014) applied to a feminine action on the narrative, in O Cortiço. Two chapters presented defend these correlations on the intrigue, through a transitory critic that when profaned the image of a realistic woman, show the presence of trace residues of a creole culture already current in the Country of America , between centuries XIX and XX